Calico Girl - Nolen, Jerdine (Simon & Schuster Books for Young Readers, 2018)
Presents a historical novel based on true accounts of the Civil War. In 1861, the state of Virginia secedes from the Union, but a Union outpost at Fort Monroe offers refuge to escaping slaves. Twelve-year-old Callie Wilcomb follows her family there, starts studying with Mrs. Mary Peake, a teacher at the fort, and learns that she can have a say over her future, a freedom she has never known.